A Finite Element Approach to the Upper-Bound Bearing Capacity of Shallow Foundations Using Zero-Thickness Interfaces - Yu-Lin Lee; Yu-Tang Huang; Chi-Min Lee; Tseng-Hsing Hsu; Ming-Long Zhu (Applied Sciences, 2025)
This study presents a robust numerical framework for evaluating the upper-bound ultimate bearing capacity of shallow foundations in cohesive and C-phi soils using a self-developed finite element method. The model incorporates multi-segment zero-thickness interface elements to accurately simulate soil discontinuities and progressive failure mechanisms, based on the Mohr–Coulomb failure criterion. In contrast to optimization-based methods such as discontinuity layout optimization (DLO) or traditional finite element limit analysis (FELA), the proposed approach uses predefined failure mechanisms to improve computational transparency and efficiency. A variety of geometric failure mechanisms are analyzed, including configurations with triangular, circular, and logarithmic spiral slip surfaces. Particular focus is given to the transition zone, which is discretized into multiple blocks to enhance accuracy and convergence. The method is developed for two-dimensional problems under the assumption of elastic deformable-plastic behavior and homogeneous isotropic soil, with limitations in automatically detecting failure mechanisms. The proposed approach is validated against classical theoretical solutions, demonstrating excellent agreement. For friction angles ranging from 0° to 40°, the computed bearing capacity factors Nc and Nq show minimal deviation from the analytical results, with errors as low as 0.04–0.19% and 0.12–2.43%, respectively. The findings confirm the method’s effectiveness in capturing complex failure behavior, providing a practical and accurate tool for geotechnical stability assessment and foundation design.